Increase in plasma beta endorphins precedes vasodepressor syncope. Issue 6 (June 1994) - Wallbridge, D. R.; MacIntyre, H. E.; Gray, C. E.; Denvir, M. A.; Oldroyd, K. G.; Rae, A. P.; Cobbe, S. M.
Abstract : BACKGROUND--Endogenous opioids have a tonic inhibitory effect on sympathetic tone and have been implicated in the pathophysiology of vasodepressor syncope. Plasma beta endorphin concentrations increase after vasodepressor syncope induced by exercise or by fasting. AIMS--To take frequent samples for plasma beta endorphin estimation during tilt testing, and to determine whether plasma beta endorphin increased before the start of syncope. PATIENTS--24 patients undergoing tilt testing for investigation of unexplained syncope. SETTING--Tertiary referral centre. METHODS--Blood samples were obtained during 70 degrees head up tilt testing. Plasma beta endorphin concentrations were estimated by radioimmunoassay (mean(SD) pmol/l). RESULTS--Patients with a positive test showed a rise in beta endorphin concentrations before syncope (baseline 4.4(1.5) v start of syncope 8.5(3.1), p < 0.002). In contrast, patients with a negative test showed no change in beta endorphin concentrations (baseline 3.4(1.0) v end of test 4.5(2.3), NS). After syncope all patients showed a large secondary increase in beta endorphins (32.3(18.6)). CONCLUSION--An increase in plasma beta endorphins precedes vasodepressor syncope. This finding supports a pathophysiological role for endogenous opioids.